«Катинський розстріл» як об’єкт дослідження воєнної кримінології - Сокуренко, В.В.; Sokurenko, V.V.; ORCID: http://orcid.org/0000-0003-4377-982X (Південноукраїнський правничий часопис. - 2022. - № 3. - С. 207-214, 2022)
Досліджено воєнно-кримінологічний аспект Катинського злочину, вчиненого радянським тоталітарним режимом навесні 1940 р. Виявлено передумови, причини та мотивацію вчинення даного воєнного злочину. Висвітлено процес підготовки та вчинення Катинського розстрілу. Вивчено основні кількісні та якісні показники, що характеризують даний злочин (рівень, динаміка, географія). Проаналізовано систему заходів, що здійснювалися для висвітлення (історична правда) та розслідування даного злочину протягом 80-річного періоду після його вчинення.

The article reveals issues related to the war crime committed by representatives of the military-political leadership and military personnel of the Soviet totalitarian regime – the mass execution of Polish prisoners of war in 1940. It shows the close connection and continuity in the commission of war crimes between the USSR and the Russian Federation, which continues the aggressive war against Ukraine.The prerequisites and possible reasons, the motivation of this crime on the part of Stalin and then the Soviet criminal elite are being analyzed.The main aspects of the preparation and commission of the specified war crime are covered in detail. Among other things, the author relies on a wide range of historical documents, including the testimony of direct participants in the Katyn shooting and the decision of the European Court of Human Rights. Stalin’s totalitarian regime war crimes are studied in interaction and interdependence with the political, social, and ideological spheres of the life of the Soviet society at that time. Criminological perception organically includes the knowledge content itself where the subjective factor is brought by the object of scientific research, as well as the psychology and worldview of the main Soviet political and war criminal – Joseph Stalin. The human factor explains the attachment of many semantic values and formulations to specific historical conditions. The topic is acutely relevant from a political and scientific point of view. Until today, this problem has been elaborated only in the historical aspect. The world political and scientific community, in contrast to the Russian propaganda machine and diplomacy, considers the fact that the USSR committed a war crime, which consisted of the shooting of Polish citizens in the spring of 1940 (Katyn shooting), as indisputable. The current war crimes committed by Russia in Ukraine (in Butcha, Kupyansk, Lyman and Olenivka) are a continuation of the criminal policy of the USSR. The Katyn massacre had its own characteristics. If previuosly the Soviet terror was directed against its own citizens, in this instance it is against citizens of another state, as we see, this is happening now during the Russian aggression against Ukraine.Unarmed prisoners were shot, that is antihumane and anti-civilization in its nature.

Исследован военно-криминологический аспект Катынского преступления, совершенного советским тоталитарным режимом весной 1940 г. Выявлены предпосылки, причины и мотивацию совершения данного военного преступления. Освещен процесс подготовки и совершения Катынского расстрела. Изучены основные количественные и качественные показатели, характеризующие данное преступление (уровень, динамика, география). Проанализирована система мероприятий, которые осуществлялись для освещения (историческая правда) и расследования данного преступления в течение 80-летнего периода после его совершения.
Katyn shooting as an object of study of military criminology
Сокуренко, В. В. «Катинський розстріл» як об’єкт дослідження воєнної кримінології / Сокуренко В. В. // Південноукраїнський правничий часопис. - 2022. - № 3. - С. 207-214. - DOI: https://doi.org/10.32850/sulj.2022.3.33.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Україна. Ukraine. Украина; історично-порівняльний аспект; historical and comparative aspect; исторически-сравнительный аспект; воєнно-кримінологічний аналіз; military and criminological analysis; военно-криминологический анализ; воєнна кримінологія; military criminology; военная криминология; Друга світова війна; Катинський розстріл; Katyn execution; Катынский расстрел; польські військовополонені; Polish prisoners of war; польские военнопленные; воєнний злочин; war crime; военное преступление